The Struggle Of Assassin To Overcome Identity Crisis As Seen In Robert Ludlum’s The Bourne Ultimatum - Raflis, Raflis; Natalia Baeha, Niata (Jurnal Ilmiah Pendidikan Scholastic, 2025)
The title of this research is “The Struggle of Assassin to Overcome Identity Crisis Seen in Robert Ludlum’s The Bourne Ultimatum.” The problem of this research examines the psychological and moral journey of Jason Bourne, the protagonist of The Bourne Ultimatum by Robert Ludlum, as he grapples with an identity crisis triggered by amnesia and his past as a trained killer. The author uses Erik Erikson’s psychosocial development theory to analyze Bourne’s struggle in finding himself and his quest for redemption. The researcher explores how Bourne’s amnesia, a result of the CIA mind control program, forces him to confront a past he does not remember, filled with violence and morally ambiguous actions.This narrative reveals the psychological burden of being an armed individual, stripped of personal identity, and forced to operate solely as a tool for the state. Through his interactions with allies and foes, Bourne wrestles with the consequences of his actions and the ethical implications of his existence. This research analyzes how he confronts his past, seeks to understand his true identity, and ultimately attempts to free himself from CIA control, demonstrating human desire for self-determination and potential for redemption even amidst profound trauma.The research concludes by highlighting the profound impact of identity crisis on an individual’s mental and moral development, showing how even a trained killer can overcome fractured self-perceptions and find meaning in a life marked by violence and manipulation.